Contextualization of Da'wah based on the Civil Society Concept in Kroya - Khusnul Khotimah; Asep Amaluddin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This paper is motivated by the concept of Dakwah carried out by Rasulullah SAW as the basis for building independence, openness, freedom, mutual respect, and religious pluralism. This study aims to present the concept of da'wah based on civil society in Kroya District. The research focused on three villages: Bajing, Karangmangu, and Ayamalas Villages. This type of research is descriptive qualitative using a phenomenological approach, collecting data using participant interview techniques, observation, and documentation. The results of the study concluded that in Kroya Subdistrict, the concept of civil society (civil society) had been applied in preaching. This can be seen as adjustments and compromises between civil society and the government in social and economic matters. The phenomenon of civil society in Kroya is implemented in the form of (1) independence in managing its social groups; (2) there is freedom and focus on community participation as subjects in managing their social groups so that there is no monopoly and intervention from the government; (3) cooperation in creating a healthy and conducive environment; and (4) religious pluralism. The implications of this research are expected to be an alternative solution for preachers so they can practice the concept of civil society in society in dealing with social, economic, and religious plurality problems.